The EURAGE Group: examining ageing and ageism in context through the European Social Survey - Vauclair, C.-M. (2014)
The experience of ageism has important health implications for older adults. Yet, to date very little is known about the interplay of psychological and contextual factors in fostering ageism. This paper presents research conducted by EURAGE (European Research Group on Attitudes to Age) which aims to study the experience of ageism and age prejudice from a multilevel perspective. EURAGE is an international group of researchers with members from the Health for All group at the Centre for Research and Social Intervention (CIS-IUL, Portugal) and the Centre for the Study of Group Processes at the University of Kent (UK). Members of EURAGE designed the Experiences and Expressions of Ageism Module in Round 4 of the European Social Survey (ESS) which is perfectly suited for multilevel analyses. The multi-level approach is briefly outlined as well as some of EURAGE’s key findings to date. Implications for policy and social interventions are briefly discussed.